Tracking an Eruptive Intermediate Prominence Originating from the Farside of the Sun - Qingmin Zhang; Wenwei Pan; Beili Ying; Li Feng; Yiliang Li; Xiaoli Yan; Liheng Yang; Ye Qiu; Jun Chen; Suli Ma (The Astrophysical Journal)
In this paper, we carry out multiwavelength and multiview observations of the eruption of an intermediate prominence originating from the farside of the Sun on 2023 March 12. The southeast footpoint of the prominence is located in NOAA Active Region 13252. The eruption generates a B7.8 class flare and a partial halo coronal mass ejection (CME). The prominence takes off at 02:00 UT and accelerates for nearly 3 hr. Rotation of the southeast leg of the prominence in the counterclockwise direction is revealed by spectroscopic and imaging observations. The apex of the prominence changes from a smooth loop to a cusp structure during the rising motion, and the northwest leg displays a drift motion after 04:30 UT, implying a writhing motion. Hence, the prominence eruption is most likely triggered by ideal kink instability. For the first time, we apply the Graduated Cylindrical Shell modeling in 3D reconstruction and tracking of the prominence for nearly 2 hr. Both the source region (110°E, 43°N) and northwest footpoint (162°E, 44°N) are located. The edge-on and face-on angular widths of the prominence are ∼6° and ∼86°, respectively. The axis has a tilt angle of ∼70° with the meridian. The heliocentric distance of the prominence leading edge increases from ∼1.26 R _⊙ to ∼2.27 R _⊙ . The true speed of the CME increases from ∼610 to ∼849 km s ^−1 .